Adoption of the Supplemental Food for School Children Program at Kulon Progo City - Andi Yuniarsy Hartika; Safira Ainun Ulumiyah (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
One of the national programs is providing Supplementary Food for School Children, which was launched to accelerate the achievement of national development goals. This complete food-based program was the first to be carried out in Kulon Progo Regency; in the previous year, this supplementary food program was provided in the form of snacks. This research aims to explore the adoption of the Supplementary Food for School Children program in Kulon Progo Regency. This research used a qualitative design with a case study approach. The selection of informants used a purposive sampling technique. Data collection is done by in-depth interview method and focus group discussion. The validity of the data is done by using source triangulation, member checking, and peer debriefing. This aspect of adoption consists of the program implementer's intention to adopt a program, how the activity implementer tries to implement a program and implements the innovations needed for program development. This is demonstrated by their being able to prepare a team to implement the Supplementary Food for School Children program in schools consisting of cooks and administrative staff, prepare the facilities and infrastructure for implementing the program, and carry out initial anthropometric measurements of school children. Schools receiving the Supplementary Food for School Children program show that they are ready and able to adopt this new program in their respective school settings